ONTOLOGIA PARA RASTREABILIDADE NA CADEIA PRODUTIVA DE SEMENTES - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
Ontologies represent the knowledge and are linked to technological developments. In agribusiness, the use of traceability increases the safety of their products and their quality. Quality assurance and process improvement is essential for seed producers. The rate of use of certified and inspected seed has grown and characterized by high competitiveness. This dissertation presents the development of ontology for quality assurance and process improvement through knowledge representation in seed production. The acquisition of knowledge was conducted by surveying Laws, regulations and standards pertaining to seed production. For the process of ontology development was used the tool Protégé, merging metodologies such as Enterprise, Methontology, On-to-Knowledge, Ontology's Development 101 Guide. As results, a system of knowledge representation and its vocabulary are presented, describing the ontology terms, classes, hierarchies, properties, restrictions and instances. One of the contributions of this research is the methodological route, enabling obtainment of main domain terms in the ontology and taxonomy generated. Traceability related to seed certification provides information that require effective control by seed companies. The creation of ontology reinforces the use of the definition of domain knowledge as information management tool, quality and transparency for entire production chain.
Keywords: ontologia; rastreabilidade; sementes; gestão; ontology; traceability; seeds; management; CNPQ::CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO